EGO IDENTITY AND ITS RELATIONSHIP TO POSITIVE THINKING AND HOPE AMONG THE STUDENTS OF SETIF 2 UNIVERSITY - BOUAOUD, Asma (International Journal of Psychosocial Rehabilitation, 2022)
This study aims to reveal the relationship between the ego identity and both positive thinking and hope among a sample of students from the University of Setif 02. The study included 217 male and female university students. The researcher employed three scales as research tools the Binion and Adams Ego Identity Scale (1998), the Abdel-Sattar Ibrahim Positive Thinking Scale (2010), and the Snyder Hope Scale (2011). The researcher also followed the descriptive correlative approach. The study yielded the following findings. The students of Setif University 2 have an average level of ego identity. The students of Setif University 2 have a high level of positive thinking and hope. - There is a statistically significant correlation at the level of significance (0.01) between the ego identity and positive thinking among the students of Setif University 2. There is a statistically significant correlation at the level of significance (0.01) between the ego identity and hope among the students of Setif University2. Through the results that have been achieved, we recommend paying attention to positive variables such as positive thinking and hope in the field of developing the ego identity of young people.